Fertilizer recommendations based on soil-nitrogen levels - a total nutrient model - Smith, Joyotee; Umali, Gloria (Wiley, 1984)
Tropical rice obtains a major portion of its N uptake from the soil as opposed to fertiliser nitrogen. Therefore N‐fertiliser recommendations should be based on the availability of soil nitrogen. This can be done by applying a total nutrient model, developed by Hildreth, which estimates yield as a function of an aggregated nitrogen variable incorporating both soil and applied N. This paper incorporates recent work on the quantification of available N, by soil scientists, into the total nutrient model to provide farm specific optimal N‐rates tailored to soil nutrient availability. The methodology, however, is only applicable to samples characterised by a high degree of internal homogeneity.